STRATEGI KOMUNIKASI PADA SINIAR “CURHAT BANG” DALAM KANAL YOUTUBE DENNY SUMARGO - Islamiah, Rahma Nadia; Pujiastuti, Rahayu (Universitas Wiralodra, 2025)
Communication carried out by sources and presenters in podcasts requires certain communication strategies so as not to cause misunderstandings when understanding the message. Based on this, the aim of this research is to describe the form of communication strategy in the